Monopelopia caraguata (Chironomidae: Tanypodinae: Pentaneurini) and Phytotelmatocladius delarosai (Chironomidae: Orthocladiinae): Two phytotelmatous chironomids distributed from Florida to Argentina - Siri, Augusto (2014)
Phytotelmata are structures present in terrestrial plants such as modified leaves, leafaxils, flowers, stem holes or depressions, open fruits and fallen leaves. These structures allow water to impound and are more common in tropical areas where plant diversity and rainfall are higher (Fish 1983). The phytotelmata provide a suitable habitat where immature chironomids are common inhabitants. In this contribution, the occurrence of the chironomid species Monopelopia caraguata Mendes et al. (Chironomidae: Tanypodinae: Pentaneurini) and Phytotelmatocladius delarosai Epler (Chironomidae: Orthocladiinae) are reported in Argentina for the first time.